ANALISISMASALAHDALAMPELAKSANAANPEMBELAJARAN GEOGRAFIBELAJARONLINEDI MASACOVID-19 SMAN 9 PONTIANAK - Nelly Apriana Gustin; Agus Sastrawan; Putri Tipa Anasi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to analyze student learning problems in the implementation of online geography learning during the COVID-19 pandemic in class X IIS SMA Negeri 9 Pontianak. This study uses a qualitative descriptive research method with a case study form. In this study there were 8 students who were involved as informants, as well as strengthening questionnaires and interviews with geography teachers and assistant principals in academic and curriculum fields. The results of this study there are student learning planning factors such as the quota that is not sufficient to download geography subject matter so that students experience learning difficulties and learning models that make Geography subjects become bored while online due to the COVID-19 pandemic. This study also provides an evaluation to overcome learning problems during the COVID-19 , including teachers making follow-up programs for students who are limited by living networks in their village areas, creating remedial programs, warning students who do not do assignments or practice questions during learning at home, the teacher increases student motivation by varying the method of teaching lectures by applying other platform media such as zoom, providing free quotas.Keywords: Covid-19 Pandemic, Geography Learning, Problem Analysis